2020
DOI: 10.1177/2380084420934731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flap Design for Enamel Matrix Derivative Application in Intraosseous Defects

Abstract: Objective: To systematically review the literature addressing the focused question: What is the effectiveness of different surgical and nonsurgical procedures combined with enamel matrix derivative (EMD) on clinical, radiographic, and patient-centered outcomes in intraosseous defects? Methods: Electronic (Medline, Scopus, and Cochrane databases) and hand literature searches were performed for studies including at least 1 treatment arm where EMD had been applied according to 1 of the following procedures: modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…However, further studies are needed to comparatively evaluate the clinical effectiveness of different flap designs when treating SDs with and without EMD. In this respect, a recent systematic review on intraosseous defects showed that the use of EMD is optimized when the lesion is surgically accessed by SFA [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further studies are needed to comparatively evaluate the clinical effectiveness of different flap designs when treating SDs with and without EMD. In this respect, a recent systematic review on intraosseous defects showed that the use of EMD is optimized when the lesion is surgically accessed by SFA [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The basic principle underlying the SFA is the elevation of a single flap (i.e., on the buccal or oral aspect only, depending on the main extension of the defect) to access the defect, leaving the interproximal supracrestal soft tissue intact [15][16][17][18][19][20][21][22][23][24][25][26]. In the regenerative treatment of intraosseous defects, SFA was associated to greater clinical results (in terms of CAL gain and intrabony component reduction) when compared to double flap approaches (DFA) based on papilla preservation techniques [27].…”
Section: Introductionmentioning
confidence: 99%
“…The adjunctive application of enamel matrix derivative (EMD) on the surgically exposed root surface is well established in regenerative periodontal therapy for the treatment of deep residual sites associated with intrabony and furcation defects and has been shown to promote significant additional gain in clinical attachment levels and enhanced reduction of probing pocket depths (Cortellini & Tonetti, 2015;Miron et al 2016;Nibali et al 2020;Jepsen et al 2020;Trombelli et al, 2020). Positive effects were also observed in supra-alveolar periodontal defects (Jentsch & Purschwitz, 2008;Di Tullio et al, 2013;Graziani et al 2014).…”
mentioning
confidence: 99%
“…There is conflicting data on whether EMD + graft material results in more CAL gain and greater PPD reduction than EMD alone. A recently published meta‐analysis looked at the treatment of infrabony defects using either EMD or EMD + graft material and differentiated the treatment outcome by flap design (Trombelli et al, 2021). They reported that EMD + graft material resulted in more CAL gain in minimally invasive variants (EMD: 3.69 mm; EMD + graft: 4.10 mm) and papilla preservation variants (EMD: 3.08 mm; EMD + graft: 3.65 mm) than EMD alone.…”
Section: Discussionmentioning
confidence: 99%